Daniel O'Leary and the Sporting Experiences of Irish Immigrants in the United States. Issue 1 (2nd January 2021) - Murtha, Ryan; Hunt, Thomas M.
ABSTRACT: During the 1870s, Daniel O'Leary was the biggest sporting star in the United States. The champion race-walker (or pedestrian, to use the language of the times) was renowned for his speed and his endurance, and travelled the country from San Francisco to New York to put on athletic displays for massive crowds. The newspapers held O'Leary up as an American hero, despite the fact that he was a recent immigrant from Ireland. In this article, we examine the factors that allowed O'Leary to transcend his immigrant status in an era when many others had trouble doing the same. It took a series of temporal accidents – O'Leary's athletic prime coinciding with a period of relatively favourable views of the Irish, coupled with the flash-in-the-pan popularity of six-day pedestrian races – but in the end Dan O'Leary transformed in the public eye from Irish-American to American. Using newspaper reports and editorials, we can see how the way he was described changed as he grew more successful. Thus, O'Leary stands as evidence not just that sport was used as a tool of assimilation as early as the 1870s, but also that the press had remarkable power to decide who was and was not American.